Psychoanalytic Exploration of Sisterhood among Brown’s The Dancing Girls of Lahore and Saeed’s Taboo! The Hidden Culture of a Red Light Area - Iftikhar, Hania; Raza, Noor ul Ain; Asif, Fatima (Pakistan Languages and Humanities Review, 2024)
Sisterhood is a forum that has provided women with the liberty to stand and fight for each other against the patriarchal society owing to the similar experiences of oppression. Based on this perspective, this study attempts to explore the bond of sisterhood among the prostitutes with the help of Lacan’s theory of registers namely the imaginary, symbolic and the real along with the themes of Other and the desire. Louise Brown’s The Dancing Girls of Lahore and Saeed’s Taboo! The Hidden Culture of a Red Light Area-two ethnographic studies- have been considered to explore the bond of sisterhood, the desires/lacks of the prostitute and the red-light area as the Lacanian real to sustain the socio-symbolic order of patriarchal Pakistani society. Owing to the same pattern of earning and the domination of patriarchal society, the bond of sisterhood among the prostitutes is examined as broken and shabby.